Trade Policy, Openness, Institutions (The Pakistan Development Review, 2006)
This paper examines the importance of institutions vis-à-vis openness and trade policies in determining per capita income differences across countries. Recent literature has tried to demonstrate that more open economies grow faster. On the other hand, it has also been asserted that it is not openness per se but institutions and good governance that matter in promoting growth. This paper attempts to test this hypothesis across a crosssection of nations. Unlike other papers in the field, we have tested not only for the degree of openness but also for trade policy indicators, as well as a fuller set of six institutional variables. Our broad finding is that although institutions matter, trade policies are also relevant to promoting growth, whereas openness per se has little impact on growth. JEL Classification: F15; O10. Keywords: International Integration; Economic Development.